2021
DOI: 10.1002/ima.22684
|View full text |Cite
|
Sign up to set email alerts
|

Pathological categorization of lung carcinoma from multimodality images using convolutional neural networks

Abstract: Accurate diagnosis and treatment of lung carcinoma depend on its pathological type and staging. Normally, pathological analysis is performed either by needle biopsy or surgery. Therefore, a noninvasive method to detect pathological types would be a good alternative. Hence, this work aims at categorizing different types of lung cancer from multimodality images. The proposed approach involves two stages. Initially, a Blind/Referenceless Image Spatial Quality Evaluator‐based approach is adopted to extract the sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We have compared our approach to the study presented in Ref. 34 It is applied to our public Lung-PET-CT-Dx dataset and is based on a shallow CNN model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have compared our approach to the study presented in Ref. 34 It is applied to our public Lung-PET-CT-Dx dataset and is based on a shallow CNN model.…”
Section: Discussionmentioning
confidence: 99%
“…We have compared our approach to the study presented in Ref. 34 It is applied to our public Lung‐PET‐CT‐Dx dataset and is based on a shallow CNN model. The results in Table 4 show that this model performs less than our proposed model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper conducts a detailed comparison of the proposed method with the latest methods in the field of lung cancer classification. The specific comparison results in references [31][32][33][34][35][36][37][38][39][40] are presented in Table 5. The first row of the table lists key information such as the data modality, dataset source, lung cancer subtypes, sample size, algorithm models, and final accuracy.…”
Section: Accuracy Comparison Experimentsmentioning
confidence: 99%
“…Sabeena et al 20,21 investigated the performance ensemble-based stack classifier and unification of wavelet transform and CNN for efficient cervical cell classification and found that the CNN-based segmentation followed by ensemble-based stack classifier achieved the best performance for cervical cell classification. Chinnu et al 22 used Blind/Referenceless Image Spatial Quality Evaluator-based approach to extract the slices having lung abnormalities from the dataset followed by a novel shallow CNN model to detect lung carcinoma from multimodality images. Remya et al 23 proposed L-UNet and Eff-UNet architectures for segmentation of G banded metaphase chromosome images.…”
mentioning
confidence: 99%